PERSEPSI GURU KIMIA TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DI SMA NEGERI 9 MANADO - Datang, Priskila Elin; Lombok, Johny Zeth; Kumajas, Jenny (LPPM Politeknik Saint Paul Sorong, 2024)
The independent curriculum is a new breakthrough program provided by the Ministry of Education and Culture Nadiem Makariem to provide learning freedom to students and teachers in determining the learning process they are interested in. The independent curriculum is a form of improvement from the previous curriculum, namely curriculum 13 (K13). As a new education system, it must have changes in the education process compared to the previous curriculum. This has led to different positive and negative responses from teachers. For this reason, researchers are interested in describing how the perceptions of teachers, especially chemistry teachers, regarding the implementation of the independent curriculum at SMA Negeri 9 Manado. This research was conducted offline by distributing printout questionnaires to 6 chemistry teachers at SMA Negeri 9 Manado. The questionnaire in this study was analyzed using a Likert scale. The results showed that the perception of chemistry teachers regarding the implementation of the independent curriculum was classified as a good category with a percentage of 71%. Teachers agree and even strongly agree on the concept of freedom of learning which focuses on changing student character. The teachers also agree with the concept of freedom of learning offered in the independent curriculum, because students and teachers are free to choose learning media, as well as the concept of independent learning by students with a learning system that can be accessed anywhere and anytime by students. They also disagreed that character surveys for graduation requirements could